Analisis Kedisiplinan Siswa dalam Kegiatan Ekstrakurikuler Pramuka Siswa SD - Ardianto, Puput; Suryatin, Suryatin; Purnamasari, Mega Isvandiana (Scholarly Journal of Elementary School, 2021)
This study discusses the discipline attitude of students who are taught in the scout extracurricular activities. The purpose of this study was to determine the implementation of scout extracurricular activities, the process of embedded students discipline character in scout extracurricular activities, the discipline of students who take part in scout extracurricular activities, as well as inhibiting and supporting factors in scout extracurricular activities at SD Negeri 2 Ketro. This study used a qualitative research approach. The result of this research is that scout extracurricular activities at SD Negeri 2 Ketro have been carried out well and smoothly. The embedded student’s discipline character in SD Negeri 2 Ketro was carried out by implementing educational rules and sanctions. Students who talking scout extracurricular activities more disciplined than students who not talking part in scout extracurricular activities. There are inhibiting and supporting factors in scout extracurricular activities.